2013
DOI: 10.1345/aph.1r442
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Initial Monotherapy with Norepinephrine Versus Vasopressin for Resuscitation in Septic Shock

Abstract: Vasopressin was noninferior to norepinephrine for the achievement of a MAP goal in the first 6 hours from onset of septic shock. Further prospective analysis is warranted; however, the results are useful for consideration of alternative vasopressors in the setting of drug shortages.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
19
0
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 34 publications
3
19
0
2
Order By: Relevance
“…This finding is consistent with previous studies, which found that AVP doses of 0.15-0.47 units/min were needed to replace NE as the sole vasoactive agent in patients with septic shock (13,14). Despite promising retrospective data (15,16), monotherapy or early initiation of AVP at doses up to 0.06 units/min appears unlikely to be sufficient to achieve a goal blood pressure in patients with septic shock and adjunctive vasoactive therapy will be needed, which may mask the potential renal benefits of AVP.…”
supporting
confidence: 92%
“…This finding is consistent with previous studies, which found that AVP doses of 0.15-0.47 units/min were needed to replace NE as the sole vasoactive agent in patients with septic shock (13,14). Despite promising retrospective data (15,16), monotherapy or early initiation of AVP at doses up to 0.06 units/min appears unlikely to be sufficient to achieve a goal blood pressure in patients with septic shock and adjunctive vasoactive therapy will be needed, which may mask the potential renal benefits of AVP.…”
supporting
confidence: 92%
“…The scenarios for which there are physiological bases for vasopressin use may represent opportunities for restrictions in the short‐term and research in the intermediate‐to‐long term. These areas included vasopressin use in patients with severe acidemia, low serum lactate concentration, vasopressin as initial monotherapy, and those at risk for renal failure …”
Section: Discussionmentioning
confidence: 99%
“…These areas included vasopressin use in patients with severe acidemia, 20 low serum lactate concentration, 21 vasopressin as initial monotherapy, [22][23][24] and those at risk for renal failure. 24,25 The respondents' increased willingness to recommend vasopressin in patients receiving stress dose steroids when medication cost is considered is in stark contrast to the above.…”
Section: Discussionmentioning
confidence: 99%
“…Penggunaan vasopresin akan lebih cepat meningkatkan MAP daripada menggunakan norepinefrin tunggal dan nilai laktat pada kelompok vasopresin mengalami perbaikan yang lebih baik dibanding dengan norepinefrin pada jam ke-6 resusitasi. 12,13 Berdasar atas beberapa uraian dan penelitian di atas maka peneliti tertarik melakukan penelitian pemberian norepinefrin ditambah plasebo dibanding dengan pemberian norepinefrin ditambah vasopresin terhadap perubahan laktat pada pasien syok septik. Berdasar atas analisis lanjutan repeated ANOVA, dapat dilihat bahwa kadar laktat rata-rata sebelum pemberian terapi (plasebo) dengan laktat rata-rata pada pengamatan kedua (T1) memiliki selisih yang signifikan.…”
Section: Pendahuluanunclassified